2015
DOI: 10.1186/s40634-015-0030-4
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical properties of five different currently used implants for open-wedge high tibial osteotomy

Abstract: BackgroundAs several new tibial osteotomy plates recently appeared on the market, the aim of the present study was to compare mechanical static and fatigue strength of three newly designed plates with gold standard plates for the treatment of medial knee joint osteoarthritis.MethodsSixteen fourth-generation tibial bone composites underwent a medial open-wedge high tibial osteotomy (HTO) according to standard techniques, using five TomoFix standard plates, five PEEKPower plates and six iBalance implants. Static… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 25 publications
3
59
2
2
Order By: Relevance
“…TomoFix HTO plates (DePuy Synthes, Zuchwil, Switzerland) have been shown to have lower stiffness and migrate more with cyclical loading than iBalance (Arthrex GmbH, Munich, Germany), Contour Lock (Arthrex), and PEEKPower (Arthrex) implants. 20 Despite these findings, TomoFix implants (without wedge blocks) are still the gold standard in HTO treatment and have lower complication rates than short spacer plates designed by competitors. 21 In laboratory-based studies, implants that produce higher construct stiffness also generally have greater fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TomoFix HTO plates (DePuy Synthes, Zuchwil, Switzerland) have been shown to have lower stiffness and migrate more with cyclical loading than iBalance (Arthrex GmbH, Munich, Germany), Contour Lock (Arthrex), and PEEKPower (Arthrex) implants. 20 Despite these findings, TomoFix implants (without wedge blocks) are still the gold standard in HTO treatment and have lower complication rates than short spacer plates designed by competitors. 21 In laboratory-based studies, implants that produce higher construct stiffness also generally have greater fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
“…21 In laboratory-based studies, implants that produce higher construct stiffness also generally have greater fatigue resistance. 20,22,23 Clinically, however, more flexible implants can perform better in terms of healing, 24 indicating that mechanical properties such as strength and, more importantly, stiffness do not necessarily translate into improved clinical performance.…”
Section: Introductionmentioning
confidence: 99%
“…A more stable fixation system could in fact allow reduction of the non-weight-bearing time, thus reducing the negative effects on a patient's functionality and speeding up the healing process. Several studies have been performed on this topic, focusing mainly on how the stability of the construct is influenced by the type and number of screws [17,47], or by the shape or positioning of the plate [8,18,39,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Using HTO for medial compartmental KOA is currently popular because the locking plate and screws can provide excellent stability immediately after osteotomy, enabling the patient to start rehabilitation programs earlier than with the use of the traditional compression plate. Scholars have shown that MP with only the TomoFix locking plate stabilizes HTO with a medial open wedge (without LHF) and provides enough stability for bone healing [26][27][28]. However, when the lateral hinge is fractured, MP only does not provide adequate stability for bone healing at the osteotomy site and at the fractured lateral hinge.…”
Section: Discussionmentioning
confidence: 99%